EFFECT OF CATALYSTS ON THE OXIDATION PROCESSES OF ACETYLENE ALCOHOLS (Scientific journal of the Fergana State University, 2025)
In the catalytic system Cu(OTf)2/TBHP/MeCN/C6H6O2, oxidation reactions of some acetylenic alcohols containing double and triple bonds in the molecules, including hexen-4-yn-1-ol-3, decen-2-yn-5-ol-4 and 1-phenylhexen-4-yn-1-ol-3, were carried out, and methods for synthesizing a new generation of unsaturated ketones were studied. The influence of reaction time, temperature, catalyst and nature of solvent on the oxidation of selected alcohols and the formation of ketones was systematically studied. The composition, purity and structure of the synthesized compounds were proven using modern physicochemical methods. The direction, stages and mechanisms of the oxidation process reaction are proposed.